Self-assessment health state of adults in Kosovo and Metohia - Milošević Jovana; Ilić Aleksandra; Đurić Slađana; Ilić Danijela; Milošević Nenad (Praxis Medica, 2018)
Introduction: A self-assessment health condition provides a general approach to creating a picture of the health status of the population. Aim: The aim of the paper is to show the connection between different categories of self-assessed health with socio-demographic characteristics, risk factors and with the presence of one or more chronic non-communicable disease of adults in Serbian communities in Kosovo and Metohia. Method: The research was carried out as a cross section study. As an instrument for data collection, the questionnaire was applied in the 2013 Survey of the Health of the Population of Serbia (excluding Kosovo and Metohija), which is in line with the European Health Research Questionnaire. For the purposes of our research, the following variables were used; gender, age, education, working status, marital status, the presence of chronic non-communicable diseases, smoking, alcohol use and physical activity. Results: A total of 1067 respondents (51.3% of women) responded, with an average age of 42.2 (± 16.0) years. Most respondents in the survey found that they feel very good or good, a quarter of the middle (not bad or good), while their condition was poor or very poor assessed by just under 5% of respondents. Among the respondents who rated their health condition as poor or very poor, there were significantly more female respondents, middle age and 65 years of age. Also, people with primary and secondary education, economically inactive, and who are inclined to the sedentary way of life, have a poor picture of their health. The frequency of people who assess their health status as bad or very bad is the highest among respondents with two or more chronic diseases. Conclusion: Different categories of self-assessment health show a tendency to connect with different individual characteristics of adult respondents. Our results can help in creating a strategy of action and building preventive programs in a defined area.